Identificación de cuentas de collar de Margarella (Thiele, 1893) en un entierro prehistórico en la desembocadura del Río Santa Cruz (Patagonia Argentina) - Zubimendi, Miguel Ángel (2019)
In this paper we present the results of the study of malacological remains recovered in Cerro Bonete or Pillay Mahuiza 1 site (southern coast of the Santa Cruz river mouth, Patagonia) which, at the moment of the discovery, was under a real risk of destruction due to cultural and natural factors. This site corresponds to an individual burial, partially excavated and dated to ca. 1100 years AP. The methodology used in the taxonomic identification of the malacological remains is described, as well as the results of the analysis that allowed their identification as artifacts, more specifically as probable shell beads for personal ornamentation. Finally, the results are described within the framework of the existing background knowledge related to the presence of beads in the archaeological record of continental Patagonia and the Fueguian archipelago.